TUMBUHKAN KREATIVITAS DIGITAL SISWA/I DENGAN MEMBANGUN WEBSITE PORTOFOLIO INTERAKTIF DI SMAN 8 KOTA TANGERANG SELATAN - Wicaksana, Bima Arya; Muhammad Rifal Junaidi; Andri Irawan; Fadil Ramadhan; Muhammad Rahmadani; Muhammad Rizky; Rahul Beget Pandapotan Purba; Muhammad Iqbal; Rizki Fadilah (Abdi Jurnal Publikasi, 2023)
This research aims to increase students' digital creativity at SMAN 8 South Tangerang City through the development of an interactive portfolio website. Through a participatory approach involving students and teachers, this project will focus on developing web design, programming and multimedia content skills. Development steps include requirements identification, interface design, creative content integration, and regular evaluation. The hope is that this website will allow students to showcase their work and contribute to the development of learning methods that strengthen students' information technology skills and creativity at SMAN 8.